A case study analysing the dropout rate of children who are heads of households at Mandela Village in Tshwane Municipality, Gauteng Province - Mankazana, Thozama Betty (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2009.